Buying into formalization? State institutions and interlocked markets in African small-scale gold mining - Fold, N.; Jønsson, J.B.; Yankson, P. (Futures, 2014)
During recent decades, artisanal and small-scale mining (ASM) in Africa has increased tremendously. An unknown but significant part is constituted by activities that are not based on legally registered mining licenses. The division of formal and informal ASM is, however, dissolved in the marketing chain where trading channels are intertwined: traders buy from miners with and without a license. So far state institutions and civil society organizations have endeavoured to 'formalize' the informal sector by focusing on relatively isolated entry points in the ASM chain from production to consumption. This paper argues that future research and design of policy mechanisms needs to focus on the inter-linkages of actors and material flows within the complex intertwinement of the formal and informal ASM sectors. Our point of departure is the findings on interlocked markets within the literature on rural dependency relations, barriers for poverty eradication and agricultural development. The paper outlines the previous debate on formalization and maps out the territorial and organizational configuration of the present ASM gold chain in Tanzania and Ghana. On this basis we maintain that state action is inevitable and suggest possible institutional mechanisms to set up incentives for possible formalization pathways for African ASM gold chains. © 2013 Elsevier Ltd.
Keywords: Artisanal and small-scale mining; Formalization; Ghana; Gold; Interlocked markets; Tanzania; Value chains